Global weak solutions to a model of micropolar fluids with Maxwell–Cattaneo heat transfer law. (September 2016) - Hamdache, K.; Hamroun, D.; Louardani, A.
Abstract: This work is devoted to the study of a system describing the dynamics of a heated micropolar fluid under the action of an applied magnetic field. The heat transfer is subjected to Maxwell–Cattaneo law instead of the usual Fourier law. Thanks to regularization and compactness methods the global existence in time of weak solutions with finite energy has been proved.